The Principal's Innovative Strategies In Promoting The New School Vision - Azis, Abdul (The Faculty of Education and Teaching Training, 2024)
Schools' leadership must adapt to the era of societal development and digital technology with all its demands, impacts, and acceleration. One of the inevitabilities is a change in the school's vision. The new vision to become the core values ??of the school community's daily behavior and performance ethos requires innovative and strategic promotion so that the community can easily recognize, understand, and guide the attitudes and culture of school community interaction in the learning process. This research aims to describe the principal's strategic efforts in introducing a new school vision and the effectiveness of the publication media used in recognizing the vision at UPTD SPF SMP Negeri 2 Prajekan in 2022/2023. This research approach uses quantitative descriptive with random sampling, amounting to 192 respondents consisting of teachers, administrative staff, school committees, and students through a questionnaire. The research results show that (1). The strategic efforts of the school principal in introducing the school's vision at UPTD SPF SMP Negeri 2 Prajekan received a positive response from the school community with a popularity level of vision reaching 92.2%, vision acronym 90.6, understanding of vision 95.8, and user-friendly 97.4% with an average value of 94% (excellent). (2). The publication media used by the school principal in introducing the new vision of the UPTD SPF school at SMP Negeri 2 Prajekan proved effective with an average score of 97.17% (perfect) based on a criterion-referenced evaluation. Kepemimpinan di sekolah perlu mengadaptasi era perkembangan masyarakat dan teknologi digital dengan segala tuntutan, dampak, dan akselerasinya. Salah satu keniscayaan adalah adanya perubahan visi sekolah. Visi baru agar dapat menjadi nilai-nilai inti perilaku keseharian dan etos kinerja warga sekolah membutuhkan promosi yang inovatif dan strategis sehingga warga sekolah dengan mudah dapat mengenal, memahami, dan menjadi pedoman sikap dan budaya interaksi warga sekolah dalam proses pembelajaran.Tujuan penelitian ini adalah mendeskripsikan upaya-upaya strategis kepala sekolah dalam mengenalkan visi baru sekolah dan efektifitas media publikasi yang digunakan dalam pengenalan visi di UPTD SPF SMP Negeri 2 Prajekan tahun 2022/2023. Pendekatan penelitan ini menggunakan deskriptif kuantitatif dengan random sampling yang berjumlah 192 responden terdiri dari guru, tenaga administrasi, komite sekolah, dan siswa melalui angket. Hasil penelitian menunjukkan bahwa (1). Upaya-upaya strategis kepala sekolah dalam mengenalkan visi sekolah di UPTD SPF SMP Negeri 2 Prajekan mendapat respon positif dari warga sekolah dengan tingkat popularitas visi mecapai 92,2 %, akronim visi 90,6, pemahaman visi 95,8, dan ramah pengguna (user friendly) 97,4% dengan nilai rata-rata sebesar 94% (sangat baik). (2). Media publikasi yang digunakan kepala sekolah dalam mengenalkan visi baru sekolah UPTD SPF SMP Negeri 2 Prajekan terbukti efektif dengan pencapaian rata-rata nilai sebesar 97,17% (sangat baik) berdasarkan penilaian acuan kriteria (citerion referenced evaluation).